Fiqh Rulings Based on Modern Communication Select Mode (NTU journal for Administrative and Human Sciences (JAHS), 2022)
This research deals with the statement of jurisprudential of important social and family issues that are carried out through modern means of communication, The research included a statement of the concept of modern means of communication and its types, And an explanation of the Judgment of acquaintance and the establishment of friendships between a man and a woman, the judgment on looking at pictures of women, The Judgment on slander, insult and cursing through modern means of communication, and then a statement of the most important results extracted from the research